Răspunsuri

2014-08-14T14:33:43+03:00
 1) a*(b+c)= ab+ac =  -2/5 + 1/3  aducem la acelasi numitor

(-6 +5)/15= -1/15

20 a(b-c)= ab-ac=  -2/5 -1/3  aducem la acelasi numitor

(-6-5)/15=  -11/15
1 3 1
2014-08-14T14:41:17+03:00
1) a*(b+c) = a*b + a*c =  ^{3)} (-2/5) + ^{5)} (1/3)
                                 = -6/15 + 5/15
                                 = -1/15
2) a*(b-c) = a*b - a*c = ^{3)} (-2/5) - ^{5)} (1/3)
                               = -6/15 - 5/15
                               = -11/15